Nitrogen fertilization can mitigate cotton yield loss by temporary shading at early flowering - Raphael, Juan P.A. [UNESP]; Echer, Fábio R.; Rosolem, Ciro A. [UNESP] (Elsevier, 2022)
Cotton (Gossypium hirsutum L.) yield is decreased under low radiation, but there are few reports on possible interactions of N fertilizer application and light limitation on cotton production. The objective of this work was to evaluate growth, yield components, and boll distribution in cotton as affected by N rates under light restriction. Three experiments were conducted for two years in Central (Primavera do Leste and Chapadão do Sul) and Southeastern (Itapeva) Brazil. Cotton plants were shaded at early flowering to a 42 % reduction in global radiation for 16–25 days. Four N rates were used in Primavera do Leste and Itapeva; and three N rates and two genotypes, an early- (FM 906GLT) and a late-maturing (FM 983GLT) cultivar, were used in Chapadão do Sul. Shading decreased lint yield by 10 % in Primavera do Leste and by 12 % in Chapadão due to 24 % and 32 % reduction in boll number at the lower third of the plant, respectively. In Itapeva, the number of bolls at the lower fruiting branches was decreased 19% by shading, but a 10% lint yield reduction was observed only with 35 kg ha−1 of N. As to the main effects, lint yield and number of bolls increased with N rates up to 155, 142 and 105 kg ha−1, depending on the site. Lint yield of shaded plants was more responsive to higher N rates, which also increased plant height, number of bolls and the main stem node number of the last fruiting branch. Cotton cultivars had similar lint yields despite differences in boll distribution. At lower fruiting branches, the early-maturing cultivar showed an average boll number 59 % higher, but the late one produced 81 % and 63 % more bolls on the upper branches at 105 and 185 kg ha−1 of N, respectively. We concluded that N-deficiency inhibited the recovery of cotton from losses caused by shading, whereas a high-N availability minimizes damages after shading during blooming.
Keywords: Gossypium hirsutum L.; Light stress; Nitrogen fertilization; Yield components